Gestión administrativa de la dirección de educación continua de la Universidad Técnica de Cotopaxi y su oferta académica. - Alvarez Ortiz, Jorge Luis (2023)
The research purpose project contribute Administrative Management improvement at Departamento de Educación Continua through strategies development that help to complement carried out activities, which constitute, an important tool that allow more adequate organization, where courses, programs and other offered activities will have greater reception. Therefore, the used methodology was descriptive and bibliographic, in addition, survey technique was used through a questionnaire made to graduates, teachers and Technical University of Cotopaxi staff, where, according to obtained results, was determined these strategies at Departamento de Educación Continua, allows them having better activities control and an adequate segregation of functions in order to comply with their proposed goals or objectives.